Association between Dietary Glycemic Index and Excess Weight in Pregnant Women in the First Trimester of Pregnancy - Ellery, Thais Helena de Pontes; Sampaio, Helena Alves de Carvalho; Carioca, Antônio Augusto Ferreira; Silva, Bruna Yhang da Costa; Alves, Júlio Augusto Gurgel; Da Silva Costa, Fabrício; Araujo Júnior, Edward; Melo, Maria Luísa Pereira de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To assess the association between dietary glycemic index (GI) and excess weight in pregnant women in the first trimester of pregnancy.Methods A cross-sectional study in a sample of 217 pregnant women was conducted at the maternal-fetal outpatient clinic of the Hospital Geral de Fortaleza, Fortaleza, state of Ceará, Brazil, for routine ultrasound examinations in the period between 11 and 13 weeks + 6 days of gestation. Weight and height were measured and the gestational body mass index (BMI) was calculated. The women were questioned about their usual body weight prior to the gestation, considering the prepregnancy weight. The dietary GI and the glycemic load (GL) of their diets were calculated and split into tertiles. Analysis of variance (ANOVA) or Kruskal-Walls and chi-squared (χ2) statistical tests were employed. A crude logistic regression model and a model adjusted for confounding variables known to influence biological outcomes were constructed. A p-value < 0.05 was considered significant for all tests employed.Results The sample group presented a high percentage of prepregnancy and gestational overweight (39.7% and 40.1%, respectively). In the tertile with the higher GI value, there was a lower dietary intake of total fibers (p = 0.005) and of soluble fibers (p = 0.008). In the third tertile, the dietary GI was associated with overweight in pregnant women in the first trimester of gestation, both in the crude model and in the model adjusted for age, total energy intake, and saturated fatty acids. However, this association was not observed in relation to the GL.Conclusion A high dietary GI was associated with excess weight in women in the first trimester of pregnancy.
Keywords: pregnancy; glycemic index; glycemic load; excess weight